If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2x-4)+2(5-x)=0
We simplify the equation to the form, which is simple to understand
3(2x-4)+2(5-x)=0
Reorder the terms in parentheses
+(+6x-12)+2*(5-x)=0
Remove unnecessary parentheses
+6x-12+2+*(+5-x+)=0
Reorder the terms in parentheses
+6x-12+(+10-2x)=0
Remove unnecessary parentheses
+6x-12+10-2x=0
We move all terms containing x to the left and all other terms to the right.
+6x-2x=0+12-10
We simplify left and right side of the equation.
+4x=+2
We divide both sides of the equation by 4 to get x.
x=0.5
| x-200=8x-25 | | .38=ln(y) | | 3x^2-18x+7=9 | | x-952=-20x-7 | | 3(2x-4)+3x= | | x-952=20x-7 | | -79+x=-39 | | 4x+36=x-57 | | 20x+7=x-582 | | 5n^2+10n-19=-7 | | 4x-12=8x-24 | | =200-75b | | 1=75b-200 | | x-77=-3x-9 | | 6x+3(3)=24 | | x+139=-3x-9 | | 4x^2+8x-52=-3 | | =15M-850N+0.4M^2+22P | | -7x-4=x-188 | | -7x-4=a-188 | | =20H+2.4H^2-0.01H^3 | | 6x+3(2)=24 | | =75b+200 | | 7(5a+9)+5(2+a)= | | X^2-21x+90= | | 10x^3(3x+6xy)= | | 2=2(x+4)-4(x-1) | | =75b-200 | | A^2-21a+90= | | 3x^2+33x= | | sin^2(x)=tan(x) | | 15c=56.70 |